Suppression of Mode Partition Noise in FP Laser by Frequency Modulation Non-Coherent Detection - Lei Xin (IEEE, 2022)
We propose a frequency modulation (FM) non-coherent detection (NCD) scheme, attempting to suppress the mode partition noise (MPN) in fiber-optic communication systems with the Fabry-Perot (FP) semiconductor laser as the light source. The system comprises a FM transmitter with a directly modulated FP laser and a semiconductor optical amplifier, standard single mode fiber, and a NCD receiver with an optical slope filter as the FM to intensity modulation (IM) signal convertor placed in front of a conventional photodetector. In this configuration, the MPN is converted into a random frequency deviation by the transmitter and is reduced by the slope filter after fiber transmission. The FM signal is therefore less noisy after being converted back into the IM signal. With optimized parameter selections, our simulation result shows that the FM-NCD system allows a direct transmission span of 40 km for the 10 Gbps signal at 1577 nm, and 120 km for the 25 Gbps signal at 1310 nm, respectively, as opposed to a span of only 3 km and 10 km achievable by a conventional FP laser driven IM direct detection (DD) system for the corresponding signals at the corresponding wavelengths. Remarkably, our simulation result also shows that the performance of the FM-NCD system even surpasses that of a directly modulated distributed feedback laser driven IM-DD system, in which the maximum span is around 15 km and 60 km for 10 Gbps and 25 Gbps signals at 1577 nm and 1310 nm, respectively.